A Creative Model for a Post-Treatment Group for Women With Cancer - Slakov, June; Leslie, Mary (Canadian Journal of Counselling and Psychotherapy, 2007)
A four-week experiential group for women at the British Columbia Cancer Agency offers the creative tools of art, meditation, and journal writing to focus the inner work of healing in the presence of others. The often unanticipated challenge of this transition period is our focus. This innovative therapy group uses a healing circle format, and images, metaphors, and attentive listening to facilitate the integration of change. Using comments from the participants, a brief history, framework, and overview are outlined.